Pengaruh Desain Kotak Terhadap Produktivitas Lebah Trigona sp - Erwan Erwan; Dwi K. Purnamasari; W. Agustin (LPPM Universitas Mataram, 2020)
One of the factors that effect the productivity of honey bees is the factor of temperature and humidity of the nest or stup where the bees live. A nest or stup with a maintened temperature and humidity will provide the bee comfort for live. This study discusses the effect of stup size design on the productivity honey bee of Trigona sp. This study used a Complete Random Design (CRD) with 3 stup design, namely: Horizontal, Vertical and Medium. Each design size consists of 4 replications, and each replication consists of 2 stup. Data were analyzed using by analysis of variance (ANOVA) and Duncan's test at 95% confidence level. The parameters observed were number of egg cells and pollen, weight pollen, number of honey pots and volume of honey. The results of the analysis showed that production of the medium design for number of egg cells, pollen, weight pollen, number of honey pots and the volume of honey of Trigona sp was significantly higher than vertical and horizontal design. The conclusion of this study showed that the medium stup is better used in farming system of Trigona sp.